Odd and Even q-Type Lidstone Polynomial Sequences (Contemporary Mathematics, 2024)
In this paper, we introduce two general classes of q-type Lidstone polynomial sequences. We give some characterizations of these classes, including matrix and determinate representations, generating functions, recurrence relations, and conjugate sequences. Some illustrative examples are included.
Keywords: q-Lidstone polynomials; q-difference equations; special sequences of q-polynomials; infinite matrices